The control of a state of the static and dynamical posture of a person doing physical exercises - Vitaliy Kashuba; Sergiy Lopatsky; Serhii Vatamanyuk (Kazimierz Wielki University, 2017)
Actuality. The human body, can be represented in modern science in various ways objectively characterizing its various elements. For example, it can be described in terms that characterize the microscopic and ultramicroscopic structure, as well as various qualitative and quantitative characteristics. The human posture is of great importance in general appearance of a person. Objectives of research: To learn deep the modern trends of the technology of visual screening of the status of human posture in the process of physical education. Results of research. To evaluate the status of the bioheometric profile of the human posture it was suggested to use the following parameters: the position of the head and trunk in relation to the vertical axis, the state of thoracic kyphosis and lumbar lordosis, the shape of the abdomen, the angle in the thigh and leg bioparts - for the sagittal plane; the position of the shoulders, the lower corners of the shoulder blades and pelvic bones, the waist triangles, the position of the feet - for the frontal plane. During the visual screening of the bioheometric human posture profile, the maximum number of points that could be obtained by the integral scan presented in Appendix B is 33 points (if all 11 indicators are scored at 3 points), the minimum number is 11 points (if all 11 indicators are estimated at 1 point). Conclusions. It was established that the highest and unchanged indicator of the state of the biogeometric posture profile was the assessment (both in low and middle levels) for students of 1- 4 years with the established type of posture "flat spine". The largest difference in the direction of the decrease in the assessment of the status of the biogeometric profile of posture in the frontal plane when comparing data of students of 1 - 4 courses was characteristic for the subjects with a normal posture and high status of the biogeometric posture profile, as well as for students with scoliostic posture and middle and low levels of condition biogeometric profile of posture. Assessment of the status of the biogeometric profile of the human posture in the sagittal plane also showed a tendency towards a decrease in the average number of points, regardless of the type of posture and the level of its biogeometric profile of students of 1 - 4 courses. The further research will be associated with the development of information and methodological system aimed on measuring the state of spatial organization of the human body in the process of physical education.